2009
DOI: 10.1016/j.mambio.2008.02.008
|View full text |Cite
|
Sign up to set email alerts
|

The role of olfaction and vision in the foraging behaviour of an echolocating megachiropteran fruit bat, Rousettus leschenaulti (Pteropodidae)

Abstract: Many mammals use multimodal sensory information to find their food in complex environments. We studied the roles of olfactory and visual cues in the foraging behaviour of Rousettus leschenaulti, a tongue-clicking megachiropteran bat. We conducted experiments by offering a whole fruit, mashed fruit without shape and an artificial fruit to R. leschenaulti in dim light as well as in total darkness. R. leschenaulti responded to whole guava fruit and mashed guava fruit even in total darkness, whereas, artificial fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…The refusal of E. wahlbergi individuals to feed on some invasive alien species offered to them indicates that they have strong preferences for the fruits on which they feed. Such preferences and how fruit bats discriminate and locate food, for example through olfaction (Elangovan et al 2006;Raghurm et al 2009), in a nocturnal environment should be further investigated and used as screening tools to identify potential bat-dispersed invasive alien fruits. To fully appreciate the role of fruit bats in seed dispersal and seedling recruitment, observations of their feeding behaviour must be combined with their movement patterns within and between various habitats.…”
Section: Discussionmentioning
confidence: 99%
“…The refusal of E. wahlbergi individuals to feed on some invasive alien species offered to them indicates that they have strong preferences for the fruits on which they feed. Such preferences and how fruit bats discriminate and locate food, for example through olfaction (Elangovan et al 2006;Raghurm et al 2009), in a nocturnal environment should be further investigated and used as screening tools to identify potential bat-dispersed invasive alien fruits. To fully appreciate the role of fruit bats in seed dispersal and seedling recruitment, observations of their feeding behaviour must be combined with their movement patterns within and between various habitats.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that laryngeal echolocating bats use echolocation rather than vision as major means of perceiving their environment [19], [20], [21]. However, in addition to using olfaction [22], pteropodids without the ability of laryngeal echolocation presumably rely more on vision for orientation and finding food than other laryngeal echolocating bats. Thus it is also reasonable to hypothesize that positive selection may act on Myo6 in pteropodids, as species in this lineage use vision primarily for orientation.…”
Section: Introductionmentioning
confidence: 99%
“…Microbats and the non-echolocating fruit bats (Megachiroptera) share an evolutionary history with a unique adaptation to flight and longevity [Teeling et al, 2000;Shen et al, 2010;Wilkinson and South, 2002]. Fruit bats use olfactory and visual senses for spatial orientation and navigation [Hodgkison et al, 2007;Raghuram et al, 2009] and indeed, brain regions processing visual and olfactory information are proportionally larger in fruit bats compared to insectivore bats [Barton et al, 1995;Hutcheon et al, 2002]. Most interesting is that nectarand fruit-eating lifestyles evolved independently in microbats and fruit bats [Thies et al, 1998;Hutcheon et al, 2002;Hodgkison et al, 2007], leading to convergent clustering of brain proportions in species occupying similar niches [de Winter and Oxnard, 2001].…”
mentioning
confidence: 99%